Prevention of overheating risk: assessment of a building project with lightweight construction in Austria (2019)
This contribution reports on an ongoing research effort within the project Sim4DLG to reduce the energy and resource use in the building sector via design optimisation of life cycle oriented buildings in Austria. To reduce the heating demand and overheating risk in the cold and warm seasons, a simulation-supported optimization strategy was pursued in addition to the concurrently computed mandatory Austrian energy performance certificate. This approach is applied to different building types, which are to be constructed within the project Life Cycle Habitation. Apart from the heating demand of the buildings, the indoor environment in view of the indoor temperatures was specifically examined to avoid overheating risk and to increase the thermal comfort for the occupants. Furthermore, the potential for preventing summertime overheating was explored according to the requirements of the Austrian standards. This includes an evaluation of simplified calculation method results, computed operative temperature during the course of the day as well as a comparison of the outcome with the findings of parametric simulations. The results suggest that properly dimensioned building parameters of residential buildings with lightweight constructions and low U-value building elements can improve the thermal comfort for the occupants and fulfil the requirements of the Austrian standards for indoor environment conditions.